Studies in the synthesis and in vitro hydrolysis of novel aspirin prodrugs - Moriarty, Louise (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2003)
Prolonged aspirin use has been associated with an increased risk of gastrointestinal bleeding, leading in some instances to haemorrhage and death. This thesis describes the design of aspirin prodrugs, from which aspirin might be regenerated after passage through the GI tract, thereby improving the side-effect profile of the agent. Numerous strategies investigated for the formation of true aspirin prodrugs are reviewed in Chapter 1. Of these attempts, only some of the glycolamides reported by Bundgaard et al. can be considered successful, since these compounds combine good aqueous stability with the ability to liberate aspirin (50%) in human plasma. Chapter 2 describes the design of a nitric oxide-releasing aspirin prodrug - isosorbide mononitrate aspirinate (ISMNA) - by integrating aspirin with isosorbide-5- mononitrate (IS-5-MN), which is a clinically successful long-acting nitrate. ISMNA is an effective anti-platelet agent in human, dog and rabbit. ISMNA liberated up to 78.7% aspirin in rabbit plasma.
Keywords: Pharmaceutical Chemistry, Ph.D.; Ph.D. Trinity College Dublin